Empowering Communities through Literacy Programs: A Case Study in Underserved Villages - Yasriuddin, Yasriuddin; Husain, Husriani; Sappaile, Baso Intang; Jaya, Rahmat; Karmila, Mila (Civiliza Publishing, 2025)
This study explores the transformative impact of literacy programs in underserved villages, employing a qualitative methodology to analyze the experiences of participants and stakeholders. Through in-depth interviews, focus group discussions, and participant observations, the research examines how literacy initiatives contribute to individual empowerment and community development. The findings reveal that such programs not only enhance reading and writing skills but also foster social cohesion, economic opportunities, and a sense of agency among community members. The study underscores the importance of culturally relevant and community-driven approaches in designing and implementing effective literacy interventions.